2008
DOI: 10.1631/jzus.b0720257
|View full text |Cite
|
Sign up to set email alerts
|

Drainage after total thyroidectomy or lobectomy for benign thyroidal disorders

Abstract: Abstract:Objective: This prospective randomized clinical trial was conducted to evaluate the necessity of drainage after total thyroidectomy or lobectomy for benign thyroidal disorders. Methods: A total of 116 patients who underwent total thyroidectomy or lobectomy for benign thyroidal disorders were randomly allocated to be drained or not. Operative and postoperative outcomes including operating time, postoperative pain assessed by visual analogue scale (VAS), total amount of intramuscular analgesic administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 12 publications
5
51
1
3
Order By: Relevance
“…9,18 Few studies have observed infective complications with the use of drain, but we didn't find such associations with drain use in present study. 7,17,19 Author found decreased post-operative pain in group A (without drain) which has been already reported in previous few studies. 5,7 Because of reduced pain and less discomfort, author found decreased length of hospital stay in the non-drainage group without any morbidity.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…9,18 Few studies have observed infective complications with the use of drain, but we didn't find such associations with drain use in present study. 7,17,19 Author found decreased post-operative pain in group A (without drain) which has been already reported in previous few studies. 5,7 Because of reduced pain and less discomfort, author found decreased length of hospital stay in the non-drainage group without any morbidity.…”
Section: Discussionsupporting
confidence: 74%
“…7,17,19 Author found decreased post-operative pain in group A (without drain) which has been already reported in previous few studies. 5,7 Because of reduced pain and less discomfort, author found decreased length of hospital stay in the non-drainage group without any morbidity. Morrissey et al also demonstrated similar result in their study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This fear prompts surgeons to use routine drains after thyroid surgery. Post-operative bleeding is actually quite rare and occurs only in 0.3% to 1% of patients after thyroidectomy 1,2 Many studies have suggested that drains may be blocked with clotted blood and the surgeon may not be alerted even if major bleeding occurs. In our study we did not encounter any patient with post-operative bleeding and therefore are unable to comment on this.…”
Section: Discussionmentioning
confidence: 99%